PELATIHAN PSYCHOLOGICAL FIRST AID PADA MAHASISWA PSIKOLOGI UNM - Ismalandari Ismail; Perdana Kusuma; St. Hadjar Nurul Istiqamah; Tri Sulastri; Nur Akmal (Universitas Negeri Makassar, 2023)
Psychological first aid (PFA) is a form of psychological intervention that can be given to victims of crises, such as natural disasters. Students are often involved as volunteers in disaster events, but are often more focused on distributing aid or donations. Psychological First Aid training was conducted to increase the knowledge of Marabunta Psychology UNM students who are disaster volunteers about the basic concept and application of PFA to disaster victims. The methods used in this training include lectures and role plays by the participants. The PFA training was divided into four stages including pretest, explanation of the PFA concept by resource persons, role play and relaxation, as well as posttest and evaluation. The results of the analysis of the pretest and posttest data showed that there was a significant increase in the participants' understanding of PFA knowledge.